2015
DOI: 10.1210/en.2014-1643
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Alters Offspring DNA Methylation Profiles in Human and Rat: Identification of Key Pathways Involved in Endocrine System Disorders, Insulin Signaling, Diabetes Signaling, and ILK Signaling

Abstract: Gestational diabetes is associated with risk for metabolic disease later in life. Using a cross-species approach in rat and humans, we examined the hypothesis that gestational diabetes during pregnancy triggers changes in the methylome of the offspring that might be mediating these risks. We show in a gestation diabetes rat model, the Cohen diabetic rat, that gestational diabetes triggers wide alterations in DNA methylation in the placenta in both candidate diabetes genes and genome-wide promoters, thus provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 51 publications
8
57
0
Order By: Relevance
“…Whereas the mechanisms leading to sex differences in disease risk remain unidentified, defective placental insulin signaling is common to these pregnancy complications and has been implicated in adverse fetal outcomes, especially in male individuals (1928). We hypothesized that impaired insulin signaling in the placenta, the critical and sex-specific maternal–fetal intermediary, is a mechanistic link between maternal metabolic dysfunction and male-biased neurodevelopmental reprogramming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the mechanisms leading to sex differences in disease risk remain unidentified, defective placental insulin signaling is common to these pregnancy complications and has been implicated in adverse fetal outcomes, especially in male individuals (1928). We hypothesized that impaired insulin signaling in the placenta, the critical and sex-specific maternal–fetal intermediary, is a mechanistic link between maternal metabolic dysfunction and male-biased neurodevelopmental reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired insulin action is common to these maternal metabolic conditions, where reduced insulin production is a hallmark of type 1 diabetes mellitus and impaired cellular responses to insulin are characteristic of type 2 diabetes, gestational diabetes, and obesity. Insulin dysfunction has been demonstrated in placental tissue from pregnancies complicated by diabetes, preeclampsia, intrauterine growth restriction, and inflammation (1927). Critically, then, placental insulin signaling may serve as a novel mediator of neurodevelopmental programming by maternal adversity contributing to disease risk.…”
mentioning
confidence: 99%
“…Growing evidence showed that DNA methylation disorder in some key genes is a linkage between maternal malnutrition and offspring metabolic disorder. Both in a rat model and humans, several genes in the insulin response pathway are differentially methylated in placenta exposed to gestational diabetes [38]. Maternal protein restricted diet reduced the methylation of glucocorticoid receptor (GR) promoter and enhanced GR expression in rat offspring liver.…”
Section: Discussionmentioning
confidence: 99%
“…Placental hypermethylation has also been linked to other complications of pregnancy including preeclampsia and placental mesenchymal dysplasia, both of which are associated with increased rates of FGR and fetal death (Anton et al 2014, Chen et al 2014. Interestingly, a rodent model of gestational diabetes has shown overlap between differentially methylated genes in the placenta and fetal tissues, which affect metabolic pathways (Petropoulos et al 2015). The effect of paternal obesity on fetal methylation status also warrants attention.…”
Section: Discussionmentioning
confidence: 99%